Uptake of niobium by cement systems relevant for nuclear waste disposal: Impact of ISA and chloride. (March 2022) - Çevirim-Papaioannou, Neşe; Jo, Yongheum; Franke, Karsten; Fuss, Markus; de Blochouse, Benny; Altmaier, Marcus; Gaona, Xavier
Abstract: The isotope 94 Nb ( t 1/2 = 2.04 ∙ 10 4 a) is produced during the operation of nuclear reactors due to the neutron activation of 93 Nb present in reactor vessels. Related waste streams will be disposed of in cement-based repositories for low and intermediate level wastes (L/ILW). The retention of niobium by cement was investigated using a combination of 95 Nb and natural 93 Nb. Sorption experiments assessed also the impact of iso-saccharinic acid (ISA) and chloride on Nb retention, both expected in specific L/ILW. Sorption experiments revealed a strong uptake of Nb by cement. Isotopic exchange with 93 Nb in HCP partly explains 95 Nb uptake, although sorption on C-S-H is tentatively proposed as main retention process. Sorption of Nb is weakly affected by chloride, but decreases importantly at [ISA] ≥ 10 −3 M reflecting the formation of (Ca-)Nb(V)-ISA complexes. This work provides key inputs to assess 94 Nb retention in the Safety Case context of nuclear waste repositories.